2022
DOI: 10.1111/jace.18868
|View full text |Cite
|
Sign up to set email alerts
|

Influence of novel shrinkage‐reducing polycarboxylate superplasticizer on the nature of calcium–silicate–hydrates

Abstract: Currently, a novel shrinkage-reducing polycarboxylate superplasticizer (SR-PCA) is used to control cementitious shrinkage. To clarify its mechanism when applied in cementitious materials, the influence of SR-PCA on the composition, morphology, and structure of synthetic calcium-silicate-hydrate (C-S-H), together with the interaction between SR-PCA and C-S-H at the atomic level, is investigated. For comparison, a commercial polycarboxylate superplasticizer (PCA) is also employed. The results show PCA and SR-PCA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 69 publications
(160 reference statements)
0
3
0
Order By: Relevance
“…The BEC-520 conductivity control instrument was selected to measure the rate of acceleration; NJ-160A building material net slurry mixer (Shanghai Meiyingpu Instrument and Instrument Manufacturing Co, Ltd.), measuring net slurry; JJ-5 building material sand mixer (Shanghai Meiyingpu Instrument and Instrument Manufacturing Co, Ltd.), used to measure the flowability of ASBM slurry; SS-150 scanning electron microscope (Carl Zeiss AG), accelerated voltage of 30 KV, magnification of 150,000 times, to determine hydration products of building materials; LabSpec-4 infrared spectrometer (Carl Zeiss AG), used to determine the strength of building materials; BD600-S peristaltic pump (Baoding Rafer Fluid Technology Co, Ltd.) for sample preparation. Digital display constant temperature water bath pot (Changzhou Putian Instrument Manufacturing Co, Ltd.), HH-1 type [ 11 ].…”
Section: Methodsmentioning
confidence: 99%
“…The BEC-520 conductivity control instrument was selected to measure the rate of acceleration; NJ-160A building material net slurry mixer (Shanghai Meiyingpu Instrument and Instrument Manufacturing Co, Ltd.), measuring net slurry; JJ-5 building material sand mixer (Shanghai Meiyingpu Instrument and Instrument Manufacturing Co, Ltd.), used to measure the flowability of ASBM slurry; SS-150 scanning electron microscope (Carl Zeiss AG), accelerated voltage of 30 KV, magnification of 150,000 times, to determine hydration products of building materials; LabSpec-4 infrared spectrometer (Carl Zeiss AG), used to determine the strength of building materials; BD600-S peristaltic pump (Baoding Rafer Fluid Technology Co, Ltd.) for sample preparation. Digital display constant temperature water bath pot (Changzhou Putian Instrument Manufacturing Co, Ltd.), HH-1 type [ 11 ].…”
Section: Methodsmentioning
confidence: 99%
“…14,15 Since it was invented in the 1980s, PCE has made great progress and has become one of the key components in the preparation of high-performance concrete. [16][17][18][19][20] A lot of studies [21][22][23][24] show that PCE has a better effect on shrinkage reduction of concrete than other types of water reducing agents such as naphthalene superplasticizer and aliphatic superplasticizer, but the reduction is limited. Lu 25 studied the relationship between the surface tension of PCE solution and the shrinkage of mortar, and found that reducing the surface tension of PCE solution can effectively reduce the volume shrinkage of concrete.…”
Section: Introductionmentioning
confidence: 99%
“…Polycarboxylate superplasticizer (PCE) has the advantages including high water reducing rate, low dosage, designability of molecular structure, environmental friendly influence, and so forth 14,15 . Since it was invented in the 1980s, PCE has made great progress and has become one of the key components in the preparation of high‐performance concrete 16–20 . A lot of studies 21–24 show that PCE has a better effect on shrinkage reduction of concrete than other types of water reducing agents such as naphthalene superplasticizer and aliphatic superplasticizer, but the reduction is limited.…”
Section: Introductionmentioning
confidence: 99%